Socioeconomic Gap in Education in Surabaya City Perspective (Max Weber Theory) - Krisanti, Dwina; Harianto, Sugeng (Side: Scientific Development Journal, 2024)
In fact, education is a must for every human being on this earth. Without education, we cannot know many things that exist in the hemisphere and can add to all existing knowledge. In education, a person is able to hone the brain's ability to think and reason and hone the brain is sharp in memory to accommodate all forms of educational material and knowledge so that it can be used in the future. In this study, it was found in the city of Surabaya which tends to be included in the urban education system, but not infrequently this education can only be accessed by the economy class the upper class who tend to have a good economy than the lower class who have difficulty in their economy, this case is something that needs to be explored deeper into the problems of existing social inequality, where education does not require that only the economic class is allowed to take education while there are The lower economic class is not the opinion of existing educational rights. The purpose of this research is to see whether the education system in Surabaya still views whether the upper economic class gets better facilities than the lower economic class and looks at the side of the Surabaya government itself in dealing with cases that occur. The method used to produce this research is a descriptive qualitative research where researchers dig up information through existing.